Probabilistic dynamic load flow with correlated wind sources. Issue 1 (21st September 2017) - Bie, Pei; Zhang, Buhan; Lu, Guojun; Deng, Weisi; Wang, Yong; Luan, Le; Li, Hang; Chen, Guoyan
Abstract : Correlation among different wind sources brings great challenge to probabilistic load flow (PLF) calculation, especially when different wind sources are not normal jointed. In addition, the fluctuation of wind energy output will aggravate the variation of the system unbalanced power, which makes it inappropriate to allocate all unbalanced power to a slack bus. In order to overcome the drawbacks of the existing methods, a probabilistic dynamic load flow (PDLF) model based on the joint‐moments method (JMM) is proposed. Different from the existing approaches, JMM can deal with different correlations among wind sources, which do not limit to normal jointed ones. Furthermore, this model can take the influence of the static power–frequency characteristic (SPFC) of generators and load into consideration, through which the probability distribution of the system frequency can also be obtained. The proposed algorithm was proved to be effective and accurate by applying it to the IEEE 30‐bus system and the IEEE 300‐bus system. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.